High-moisture corn with additives for finishing rations - Young, B.; Ilg, H.; Bolsen, K. (Kansas State University. Agricultural Experiment Station, 2011)
Dry corn (dry), Harvestore ensiled high-moisture corn, stave silo ensiled high-moisture corn (stave H.M.C.) and stave H.M.C. ensiled with NaOH, Cold-flo ammonia, or Silo-Best additives were evaluated in steer and heifer finishing trials. Cold-flo and NaOH H.M.C. gave slowest gains; NaOH had the highest intake and Harvestore H.M.C. the lowest, efficiency of gain favored the Harvestore H.M.C. All H.M.C. corn except NaOH was unstable in air because of high dry matter at ensiling, slow corn use, and warm temperatures. Dry matter losses and temperature rises during air exposure were highest for Cold-flo and Harvestore H.M.C.
Keywords: Beef; Corn; Finishing rations; Intake